The complex relationship between transparency and accountability: A synthesis and contribution to existing frameworks. (April 2017) - Mabillard, Vincent; Zumofen, Raphael
Accountability and transparency are of growing importance in contemporary governance. The academic literature has broadly studied the two concepts separately, defining and redefining them, putting them into various frameworks, and sometimes mistakenly using them as synonyms. Curiously, the relationship between the two concepts has been studied only by a few scholars with preliminary approaches. This theoretical article focuses on both concepts, attempting first to describe them, taking into account the various evolutions in the literature and recent developments, and also the first attempts to link the two concepts. In order to show a new approach linking the concepts, theoretical situations in which the concepts are linked are portrayed, demonstrating the need to reconsider the relationship between transparency and accountability. Consequently, a new framework amending the most recent approaches is presented, theoretically delimited and exemplified through practical cases.